The effect of scarification and soaking duration of liquid organic fertilizer (POC) of eternal lucky mushroom (JAKABA) on soursop (Annona Muricata L.) seed germination - Muhammad Zikri Pratama; Sri Ritawati; Nur Iman Muztahidin; Imas Rohmawati (Jurnal Agrotek Ummat, 2026)
The process of germination of soursop seeds can occur if the seed coat is permeable to water and sufficient water is available with a certain osmotic pressure. This study aims to determine the effect of jakaba on the germination of soursop seeds (Annona muricata L). This study used a factorial randomized block design (RAK) with 2 factors, namely scarification (S) as the first factor consisting of 3 levels including S1 = cutting half of the seed, S2 = cutting and S3 = peeling half of the seed coat. The second factor is the duration of soaking jakaba POC (P) which consists of 4 levels including P1 = 6 hours, P2 = 12 hours, P3 = 18 hours, and P4 = 24 hours. The results of this study are the combination of peeling half of the seed coat and soaking Jakaba POC for 6 hours (P1S3) is the best treatment that increases germination power up to 86.67%. On its own, peeling effectively stimulates germination, while cutting the seeds produces the longest shoots (10.21 cm). For soaking, a soaking time of 12–24 hours is most effective in accelerating germination time and supporting strong shoot growth